1973
DOI: 10.1111/j.1467-8306.1973.tb00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Green Revolution in India∗

Abstract: The introduction of hybrid seeds in India has doubled the yield of foodgrains. The High Yielding Variety Seed Program (H.V.P.) has contributed to serious interregional disparities in agriculture. Surplus production of foodgrains is not the true measure of success of the Green Revolution; many areas in India remain unaffected by this program, and are still vulnerable to famines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Borlaug and Swaminathan introduced five different HYV grains: wheat, rice, maize, sorghum, and pearl millet (bajra in Hindi). Agricultural scientists designed the HYV of each crop to respond well to fertilizers, have higher yields than indigenous varieties, withstand drought, and grow faster to allow for multiple harvests in a year (Chakravarti 1973). Initially, this new technology was mainly applied in North India, in the states of Punjab, Haryana, and Uttar Pradesh, because there was pre-existing irrigation networks (Whitcombe 1972).…”
Section: Revolution In Indiamentioning
confidence: 99%
See 3 more Smart Citations
“…Borlaug and Swaminathan introduced five different HYV grains: wheat, rice, maize, sorghum, and pearl millet (bajra in Hindi). Agricultural scientists designed the HYV of each crop to respond well to fertilizers, have higher yields than indigenous varieties, withstand drought, and grow faster to allow for multiple harvests in a year (Chakravarti 1973). Initially, this new technology was mainly applied in North India, in the states of Punjab, Haryana, and Uttar Pradesh, because there was pre-existing irrigation networks (Whitcombe 1972).…”
Section: Revolution In Indiamentioning
confidence: 99%
“…Initially, this new technology was mainly applied in North India, in the states of Punjab, Haryana, and Uttar Pradesh, because there was pre-existing irrigation networks (Whitcombe 1972). The availability of irrigation was essential to the success of HYVs because scientists found that 70% of India did not receive enough or consistent enough rainfall to support HYVs (Chakravarti 1973). The new technology spread throughout India through the "Intensive Agricultural District Programme" (IADP), a government program that involved demonstration farms, credit schemes, and the dispersal of seeds, fertilizers, and pesticides (Chakravarti 1973).…”
Section: Revolution In Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…The real momentum of wheat development was gained as amber or white grain genotypes like Kalyan Sona, Sonalika, Safed Lerma, and Choti Lerma were produced in 1967 (Dalrymple, 1974), which marked the Wheat Revolution in India. The High Yielding Varieties Programme was started by the Government of India during 1966-67, which brought about 12.8 million hectares of land under wheat cultivation (Chakravarti, 1973). Thereafter, high yielding and disease resistant varieties were released that suited various ecological and growing conditions in India.…”
Section: 4) Evolution Of Wheatmentioning
confidence: 99%